Mystery in Marketing Management Products Post COVID-19 as a Model of Survival Strategy Towards the Awakening of Micro Small and Medium Enterprises (MSMEs) in the Digital Economy Era - Rahma Wahdiniwaty; Deri Firmansyah; Asep Suryana; Dede Dede; Asep Achmad Rifa'i (Khazanah Sosial, 2022)
This research aims to find out the secret strategy applied in the marketing management of Mie Ewok Sukabumi Post COVID-19 towards the rise of MSMEs in the digital economy era. This study uses a qualitative approach with qualitative descriptive analysis and uses triangulation techniques to examine the data obtained from observations, interviews, FGDs, literature studies, and field visits. Based on the data that was collected, reduced, and the results of the FGD deepening, the findings from our analysis show that the secret survival strategy applied in Mie Ewok marketing management after COVID-19 towards the rise of MSMEs in the Digital Economy era, starting with personal branding and digital branding, digital media selection, business process strategy, online marketing, sales promotion, digital literacy readiness, and economic literacy. It is hoped that the survival strategy revealed is useful, feasible to be adopted and developed by other MSME actors to be implemented through marketing management by combining adaptability and survival in order to be able to rise again to continue to grow and have high competitiveness in the era of the digital economy. Qualitative descriptive analysis using this triangulation technique has enabled us to conduct an in-depth and detailed analysis of the business sector with the criteria of micro and small enterprises but has a narrow generalization capability for the larger business sector or industry. To overcome this limitation, future research is expected to use surveys covering the medium and large business sectors or other industries to test the findings and theories resulting from this research. The generalizations can be applied more broadly and guaranteed.